Recommendations for diagnosis, treatment, and prevention of iron deficiency and iron deficiency anemia - Iolascon, Achille; Andolfo, Immacolata; Russo, Roberta; Sanchez, Mayka; Busti, Fabiana; Swinkels, Dorine; Aguilar Martinez, Patricia; Bou-Fakhredin, Rayan; Muckenthaler, Martina; Unal, Sule; Porto, Graça; Ganz, Tomas; et al. (HemaSphere, 2024)
Iron is an essential nutrient and a constituent of ferroproteins and enzymes crucial for human life. Generally, nonmenstruating individuals preserve iron very efficiently, losing less than 0.1% of their body iron content each day, an amount that is replaced through dietary iron absorption. Most of the iron is in the hemoglobin (Hb) of red blood cells (RBCs); thus, blood loss is the most common cause of acute iron depletion and anemia worldwide, and reduced hemoglobin synthesis and anemia are the most common consequences of low plasma iron concentrations. The term iron deficiency (ID) refers to the reduction of total body iron stores due to impaired nutrition, reduced absorption secondary to gastrointestinal conditions, increased blood loss, and increased needs as in pregnancy. Iron deficiency anemia (IDA) is defined as low Hb or hematocrit associated with microcytic and hypochromic erythrocytes and low RBC count due to iron deficiency. IDA most commonly affects women of reproductive age, the developing fetus, children, patients with chronic and inflammatory diseases, and the elderly. IDA is the most frequent hematological disorder in children, with an incidence in industrialized countries of 20.1% between 0 and 4 years of age and 5.9% between 5 and 14 years (39% and 48.1% in developing countries). The diagnosis, management, and treatment of patients with ID and IDA change depending on age and gender and during pregnancy. We herein summarize what is known about the diagnosis, treatment, and prevention of ID and IDA and formulate a specific set of recommendations on this topic.
Online veröffentlicht: 15.Juli 2024
Gesehen am 13.02.2025